Shaking machine designed at Arlington Experimental Farm (1928)
View of a shaking machine designed at the Arlington Experimental Farm in Arlington, Virginia. Established by an act of Congress in April 1900, Arlington Farm served as the main field laboratory for the Bureau of Soils, U.S. Department of Agriculture, until 1941. The shaking machine was likely used in the production of fertilizer as part of the work of the U.S. Department of Agriculture's Fixed Nitrogen Research Laboratory located in Washington, D.C.
Keywords: Nitrogen fertilizer industry; United States. Bureau of Chemistry and Soils; United States. Department of Agriculture; Scientific apparatus and instruments